Comunicación entre padres e hijos y desintegración familiar en el barrio Urseza 2, sector 1 de la ciudad de Machala - Samaniego Ramírez, Karol Mabel (My University, 2019)
Many of current problems in the society is linked with of wrong management of parents with their children’s. The raising, debauchery and the little interest which show towards them. However, everything arises from insufficient communication. The present research have like a main theme, the communication between parents and children’s breakdown in the neighborhood Urseza 2, sector 1 of Machala city. It is expound the problem in this locality, which passes through an inadequate communication that exists between parents and children that brings like a consequence the family disintegration with in this locality., The objective is to analyze the factors that intervene in the communication between parents and children and their incidence in family disintegration, through the analysis of bibliographic information and field work based on the criteria of five families. The result of the review of documents and scientific articles of incensed journals where the literature that accounts for the state of the art in which the problem of family dysfunction is theoretically located, is based on the interview of five cases to which a questionnaire is applied previously. designed from under the qualitative approach, in perspective to promote reflection on the aspects that in contemporary society are gravitating so that the disarticulation of the members of the households is reflected in the increase of drug consumption, prostitution, alcoholismMany of current problems in the society is linked with of wrong management of parents with their children’s. The raising, debauchery and the little interest which show towards them. However, everything arises from insufficient communication. The present research have like a main theme, the communication between parents and children’s breakdown in the neighborhood Urseza 2, sector 1 of Machala city. It is expound the problem in this locality, which passes through an inadequate communication that exists between parents and children that brings like a consequence the family disintegration with in this locality., The objective is to analyze the factors that intervene in the communication between parents and children and their incidence in family disintegration, through the analysis of bibliographic information and field work based on the criteria of five families. The result of the review of documents and scientific articles of incensed journals where the literature that accounts for the state of the art in which the problem of family dysfunction is theoretically located, is based on the interview of five cases to which a questionnaire is applied previously. designed from under the qualitative approach, in perspective to promote reflection on the aspects that in contemporary society are gravitating so that the disarticulation of the members of the households is reflected in the increase of drug consumption, prostitution, alcoholism, delinquency, among others, which are characteristics associated fundamentally with the disintegration of the family., delinquency, among others, which are characteristics associated fundamentally with the disintegration of the family.
Muchos de los problemas actuales en la sociedad están vinculados con el mal manejo de los padres hacia sus hijos, la crianza, el libertinaje y el poco interés que estos muestran hacia ellos. Pero todo surge a partir de la insuficiente comunicación. El presente trabajo investigativo tiene como tema principal, la comunicación entre padres e hijos y desintegración familiar en el barrio Urseza 2, sector 1 de la ciudad de Machala. Se expone la problemática existente en esta localidad, la cual pasa por una comunicación inadecuada que existe entre padres e hijos, que trae como consecuencia la desintegración familiar dentro de esta localidad. El objetivo es Analizar los factores que intervienen en la comunicación entre padres e hijos y su incidencia en la desintegración familiar, a través del análisis de información bibliográfica y trabajo de campo basado en el criterio de cinco familias., el resultado de la revisión de documentos y artículos científicos de revistas incensadas donde se registra la literatura que da cuenta del estado del arte en el que se sitúa teóricamente el problema de la disfuncionalidad familiar ;además se apoya en la entrevista de cinco casos a los que se aplicó un cuestionario previamente diseñado desde bajo el enfoque cualitativo, para promover la reflexión sobre aspectos que en la sociedad contemporánea están gravitando para que la desarticulación de los integrantes de los hogares se vea reflejada en el aumento del consumo de drogas, prostitución, alcoholismo, delincuencia, entre otros, que son características asociadas fundamentalmente a la desintegración familiar.
Keywords: FAMILIA; DISFUNCIONAL; PROBLEMA; COMUNICACION